Applications of the TPOD Method in the High-Dimensional Rotor System Models with Common Faults - Lu, Kuan; Yang, Yongfeng; Yu, Hai; Jin, Yulin; Chen, Yushu (Journal of Applied Nonlinear Dynamics, 2026)
The transient proper orthogonal decomposition (TPOD) method is generalized to high-dimensional rotor system models with common faults and the efficiency of the reduced models is discussed in this paper. The method to confirm the optimal reduced rotor model for order reduction is proposed based on the physical significance of the TPOD method. The physical significance of the TPOD method can be provided by the proper orthogonalmode (POM). Three rotor models with faults are established by the Newton’s second law: the first is crack fault, the second is looseness fault and the third is the model with coupling faults. The model with coupling faults contains more complex characteristics than the other two models with single fault (looseness, crack). The TPOD method is applied to obtain the relatively optimal reduced model based on the POM energy. The efficiency of order reduction method is verified via the energy curves of POM and many other dynamical behaviors (the bifurcation diagrams, the amplitude-frequency curves, the phase curves, etc.). The optimal reduced models of the rotor systems can be obtained via applying the TPOD method on the basis of the POM energy.